TRADITIONAL FOLK MEDIA AND CLIMATE CHANGE MITIGATION MEASURES OF AGRICULTURAL LAND USERS IN OGOJA EDUCATION ZONE OF CROSS RIVER STATE, NIGERIA - Essien Cecilia Kori; Anthony Godwin Bullem; Olofu Martin Afen; Omang Theresa Nkim (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
This study examined traditional folk media and climate change mitigation measures of agricultural land users in Ogoja Education Zone of Cross River State, Nigeria. One research questions and one statement of hypothesis was formulated to guide the study. Literature review was carried out based on the variable under study. Survey research design was considered most suitable for the study. Stratified random and simple random sampling techniques were adopted in selecting the 404 respondents sampled for the study. A validated 15 item four point modified Likert scale questionnaire was the instrument used for data collection. The reliability estimate of the instrument of 0.84was established using Cronbach Alpha method. Simple linear regression statistical tool was used for data analyses. The hypothesis was tested at 0.05 level of significance. The findings revealed that traditional folk media haa a significant influence on climate change mitigation measures in the study area. It was recommended that awareness creation on traditional plays as a climate change awareness strategy should be improved and made an integral part of community norms and values by community elders and chiefs.